1983
DOI: 10.1007/bf00006071
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal indicator potential of the Asiatic clam (Corbicula fluminea) in artificial stream systems

Abstract: The potential of the Asiatic clam, Corbiculafluminea, as a bioindicator of cadmium, copper, and zinc was studied during 28-day exposures in field artificial streams receiving river water on a once-through basis. Copper, at aquatic concentrations of 0.016 and 0.057 mg 1 , showed the greatest degree of tissue uptake and had bioconcentration factors (BCF) of 22 571 and 17 720, respectively. A significant correlation (coefficient = 0.639) was observed between water concentration and tissue accumulation. Cadmium wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 17 publications
3
20
0
1
Order By: Relevance
“…Kraak et al (1993) suggested that every increase in dissolved Cd concentration in water resulted in a significant increase in its concentration in mussels. The same was observed by Graney et al (1983) and Timmermans (1993). Consequently, if Cd were available in the environment, mussels would probably accumulate it.…”
Section: Discussionsupporting
confidence: 85%
“…Kraak et al (1993) suggested that every increase in dissolved Cd concentration in water resulted in a significant increase in its concentration in mussels. The same was observed by Graney et al (1983) and Timmermans (1993). Consequently, if Cd were available in the environment, mussels would probably accumulate it.…”
Section: Discussionsupporting
confidence: 85%
“…The extent of the distribution of this organism and its resistance to the lethal effects of aquatic pollutants have prompted its use as a biomonitoring organism in freshwater environments similar to efforts with bivalves (Crassostrea gigas, Mya arenaria, Mytilus edulis, and Rangia cuneata) in brackish and marine water systems (Butler, 1969;Goldberg et al, 1978;Popham et al, 1980). Graney et al (1983) demonstrated that the Asiatic clam accumulates heavy metals such as cadmium (Cd), copper (Cu), and zinc (Zn). They reported bioconcentration factor (BCF, the ratio of tissue concentration to water concentration) ranges of 358 to 631 for Zn and 17720 to 22571 for Cu when clams were exposed to these metals in laboratory artificial streams.…”
Section: Introductionmentioning
confidence: 99%
“…The 20 mg pulverized powder was digested with several acids by the following steps: (1) digested with 200 µL of hydrogen peroxide (H 2 O 2 ), 1 mL of 61% nitric acid (HNO 3 ), and 500 µL of hydrofluoric acid (HF), and heated on a hotplate at 160 • C for 30 min; (2) cooled down at room temperature for 30 min; (3) evaporated to dryness on the hotplate at 80 • C; (4) digested with 1 mL of 61% HNO 3 and heated on the hotplate at 160 • C for 30 min; (5) cooled down at room temperature for 30 min; (6) evaporated to dryness on the hotplate at 80 • C; (7) digested with 1 mL of 30% HNO 3 and heated on the hotplate at 120 • C for 10 min; and (8) cooled down to room temperature for 1 h. The digested solution was diluted by 3% HNO 3 as the solution for analysis.…”
Section: Inductively Coupled Plasma-mass Spectrometry (Icp-ms)mentioning
confidence: 99%